The Role of Emotional Intelligence, Self-Confidence, and Leadership Styles among Psychologists (Journal of Social Sciences Review, 2023)
This study aims to determine how emotional intelligence, self-confidence, and leadership styles affect how well Pakistani psychologists do their jobs. In order to do this, a sample of 210 psychologists was polled about various leadership styles, including authoritarian, democratic, and laissez-faire. The Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT), the Self-Confidence Scale (SCS), and the Leadership Styles Questionnaire (LSQ) were used to test their emotional intelligence, self-confidence, and leadership styles, respectively. Emotional intelligence and self-confidence were favourably correlated with performance, whereas authoritative leadership, democratic leadership, and laissez-faire leadership all had a favourable effect on performance. These results show that emotional intelligence, self-confidence, and how a psychologist leads significantly impact how well they do their job.
Keywords: Emotional Intelligence; Self-confidence; Leadership Styles; Authoritative; Democratic; Laissez-faire; Psychologist Performance